Indonesia 2001 kehilangan pamor. - Penerbit Buku Kompas (Jakarta : Penerbit Buku Kompas, 2001)
Economic, social, and political conditions in Indonesia; collection of articles previously published in Kompas daily.
Continues: Demokrasi, kekerasan, disintegrasi.
"April 2001."
Includes index.
Keywords: Indonesia -- Politics and government -- 1998-; Indonesia -- Economic policy -- 1998-; Indonesia -- Economic conditions -- 1997-; Indonesia -- Social conditions -- 1998-